Comparison of the Efficiency of Ultraviolet/Zinc Oxide (UV/ZnO) and Ozone/Zinc Oxide (O3/ZnO) Techniques as Advanced Oxidation Processes in the Removal of Trimethoprim from Aqueous Solutions - Moayede Taie; Abdolmajid Fadaei; Mehraban Sadeghi; Sara Hemati; Gashtasb Mardani (International Journal of Chemical Engineering)
Nowadays, advanced oxidation processes, particularly photocatalyst process and catalytic ozonation by ZnO nanoparticles, are the most efficient method of eliminating pharmaceuticals. The purpose of this study was to compare the efficiency of ultraviolet/zinc oxide (UV/ZnO) and ozone/zinc oxide (O3/ZnO) techniques as advanced oxidation processes in the removal of trimethoprim (TMP) from aqueous solutions. The process consisted of 0.6 g/L of ozone (O3), pH = 7.5 ± 0.5, TMP with a concentration of 0.5–5 mg/L, ZnO with a dose of 50–500 mg/L, 5–30 min reaction time, and 30–180 min contact time with UV radiation (6 W, 256 nm) in a continuous reactor. The high removal efficiency was achieved after 25 minutes when ZnO is used in 1 mg/L TMP under an operational condition at pH 7.5. When the concentration of the pollutant increased from 0.5 to 1, the average removal efficiency increased from 78% to 94%, and then, it remained almost constant. An increase in the reaction time from 5 to 25 minutes will cause the average elimination to increase from 84% to 94%. The results showed that the efficiency of O3/ZnO process in the removal of TMP was 94%, while the removal efficiency of UV/ZnO process was 91%. The findings exhibited that the kinetic study followed the second-order kinetics, both processes. With regard to the results, the photocatalyst process and catalytic ozonation by ZnO nanoparticles can make acceptable levels for an efficient posttreatment. Finally, this combined system is proven to be a technically effective method for treating antibiotic contaminants.